Medium and large-sized mammals from Isla Santay National of Recreation Area in western Ecuador - Torres-Domínguez, Alvaro (2022)
Isla Santay is an important Ecuadorian conservation area for native species, but with little information on mammals. Between August 2018 and January 2019, the richness and abundance of medium and large mammals was studied in two areas with different land use: undisturbed, and disturbed. We used a combination of camera trapping, direct observation, and indirect evidence (i.e. tracks, scat) for quantifying species richness. We recorded a total of six species, all observed in both zones, and three of them are currently included on the Red List of Mammals in Ecuador. In the undisturbed zone, Leopardus pardalis was the most frequently observed species and showed the highest activity; in the disturbed zone, L. pardalis and Procyon cancrivorus were the most active. Additionally, we reported the presence of Lontra longicaudis and Philander melanurus for the first time in this reserve. Several species that we expected to observe, such as Didelphis marsupialis, Nasua nasua, Eira barbara, Galictis vittata, and Herpailurus yaguarondi, were not recorded. Isla Santay presented low species richness, probably due to environmental pollution and geographic isolation. Nonetheless, Isla Santay is a critical area for the preservation of mammalian species from western Ecuador, especially for species at risk. Future research should prioritize both the preservation of ecological processes and the understanding of the negative effects of human impacts on local biodiversity.